Kinerja tenaga pelaksana gizi puskesmas di Kota Depok Jawa Barat - ADIL, Muhammad ([Yogyakarta] : Universitas Gadjah Mada, 2009)
Background: The program of community nutrition improvement has been implemented for years; however the problem of nutrition is still relatively complicated and occurs in each cycle of life from the beginning of life (fetus), infancy, childhood teenagers, adolescent and elderly. The result of the study carried out by Health Development and Research Council 2005 showed there was an indication of low performance of nutrition staff in the field. Meanwhile the community demands quality nutrition and health services. A health center is a major health facility that provides health including nutrition service to the community throughout the nation. Nutrition staff at the health center are health staff in charge of nutrition program implementation at the level of health center and they are the frontliners of nutrition program implementation in the community. They directly meet the community so that their role becomes very important. Objective: To find out the performance of nutrition staff of the health centers at Depok Municipality, Jawa Barat. Method: The study was observational with cross sectional design. Subject consisted of coordinator of nutrition program and/or nutrition staff in the field. The study was carried out from September to December 2008 at Depok Municipality, Province of Jawa Barat. Data obtained included performance of nutrition staff of the health center, individual variables, psychological variables, and organizational variables that were taken using quantitative method through questionnaire and forms and qualitative method through indepth interview. Quantitative data were processed and analyzed using univariate, bivariate and multivariate with correlation and logistic regression statistical test. Qualitative data were made into transcript and analyzed using quotation method. Result: There was significant association between individual variables and psychological variables in particular between age and motivation (r=-0.384). There was significants association between individual variables and organizational variables, in particular between the level of understanding and objective of the organization (r=0.484); between the level of understanding and organizational structure (r=0.484); between the level of understanding and supporting facilities (r=0.451); between education and human relationship (r=-0.389); between education and leadership (r=-0.389). There was significant association between individual variables and performance in particular between age and total performance (r=-0.451). There was significant association between psychological variable and performance, in particular between motivation and total performance (r=0.367). Conclusion: To improve performance of nutrition staff it was necessary to make some efforts such as fulfilling the need for staff at the health center, improving the understanding about duties and function of nutrition staff, staff refreshing through rolling, and improving motivation of nutrition staff.